PORTRAIT OF SELF EFFICACY AND CONSERVATIONMATERNITY NURSING CARE ON PATIENT WITH CERVICAL CANCER - APRILIANI YULIANTI WURININGSIH (NURSCOPE: Jurnal Penelitian dan Pemikiran Ilmiah Keperawatan, 2016)
Cervical cancer is one of the main chronic diseases in women with a variety of symptoms throughout the patient's life. The adaptation process of the symptoms is an important part which is the responsibility of patients with chronic diseases such as cervical cancer. Conservation and self-efficacy models can assist nurses through a framework based on four principles of conservation that are integrated with all four components of self-efficacy. The integration of these two models can represent the views of individual holistically, active, and independent, and involves the active participation of the patient in the nursing plan. This can help patients to manage a normal life in order to survive and improve their health status.Keywords: cervical cancer, the integration of conservation and self-efficacy theory.